Teologi Pembebasan Perempuan Perspektif Asghar Ali Engineer - Anita Juliani; Radea Yuli Hambali (Jurnal Riset Agama, 2022)
Gender inequality experienced by women is still rampant to this day. Orthodox societies often use religious teachings to perpetuate patriarchal systems. This study has the aim of discussing and knowing the challenges and rights of women in Islam. This research is very important for the current condition of women in Indonesia, because many Indonesian ulama figures have misogynistic interpretations of the Qur'anic verse. Therefore, this research is important in solving problems regarding women who are oppressed as a result of these problems. This study uses an approach that is descriptive-analytical method. The technique in this research is library study. As for the results and discussion in this study, that Asghar Ali Engineer regarding theological theology, Islam is present with a liberation mission. Therefore, and the function of women who have experts has the same opportunities and opportunities as men who have been in the Shari'a not only determined on the basis of the text of the Qur'an, but in addition to the Sunnah of the Prophet and the opinions of the fiqh (judges). . The Bible is not only normative but also pragmatic. In another sense, the Qur'an is not always normative but relevant to its era. Likewise with his teachings. Because basically, Islam brings people to justice.